A review of online intervention for Obsessive-Compulsive Disorder (OCD) - Lee, Jing Giong; Noh Amit; Shazli Ezzat Ghazali; Ponnusamy Subramaniam (Penerbit Universiti Kebangsaan Malaysia, 2020)
The aim of this paper is to summarize and discuss the existing online intervention for Obsessive-Compulsive Disorder (OCD). This paper is using the narrative approach and the search engine used include PubMed, SAGE Journals, EBSCO host and Cochrane Library. A total of 10 articles were included for this review and it categorised by authors into five online intervention programmes for OCD which are BiP OCD, OCD? Not Me!, OCD-NET, iCBT and COT. All these programmes were aimed to help the people who suffer from OCD, but the programmes might have some differences in term of the age range of the participants, the duration of the programme, and slight differences in term of the contents of the programmes and measures used. The online intervention for OCD used the principles of Cognitive Behavioural Therapy (CBT) and included the part of psychoeducation, exposure and response prevention (ERP), and relapse prevention. The contents of psychoeducation, ERP and relapse prevention, and the effectiveness of the online intervention programme for OCD will be discussed in this paper. The future research should emphasize on the development of an online intervention for OCD in Malaysia by considering the cultural and language issues in Malaysia.